Comprehensive analysis of the peanut allergome combining 2-DE gel-based and gel-free proteomics. (February 2019) - Mamone, Gianfranco; Di Stasio, Luigia; De Caro, Salvatore; Picariello, Gianluca; Nicolai, Maria Adalgisa; Ferranti, Pasquale
Abstract: In this work, we explored the "deep" seed peanut proteome by using both two dimensional electrophoresis (2-DE)-based analysis run under reducing and non-reducing condition (protein-centric) and LC-MS/MS gel-free proteomic (peptide-centric). The former approach allowed to identify high molecular weight disulfide-linked Ara h 1 and Ara h 3 heteroligomers and Ara h 1 homoligomers linked through covalent bonds other than disulfides. The occurrence of these protein complexes revealed natural interactions between Ara(s) subunits with a possible involvement in the allergenic potential of peanut. The second approach, also referred to as shot-gun proteomics, allowed the identification of 149 gene products, including low-abundance proteins escaped the 2-DE detection. Interestingly, we identified 60 proteins never catalogued previously. The complementary exploitation of two proteomic approaches enabled the access to new relevant information about the complexity of the peanut proteome, with special emphasis to the complement of allergens (allergome). Graphical abstract: Unlabelled Image Highlights: High MW disulfide-linked multimers of Ara h 1 and Ara h 3 were characterized. Ara h 1 oligomers aggregated via covalent bonds other than disulfides. 2DE and shot-gun proteomics were complementary to resolve the peanut allergome. Identification of 149 peanut seed gene products.